The effect of sex education on the marital relationship quality of pregnant women - Ali Navidian; Shahindokht Navabi Rigi; Mahmoud Imani; Parvin Soltani (Tehran University of Medical Sciences, 2016)
Background & Aim: The physiological and psychological changes in pregnancy, can affect the lives of couples. The present study aimed to determine the effect of sex education on the marital relationship quality of pregnant women. Methods & Materials: This study is a quasi-experimental. In this study, 100 pregnant women referred to health centers in Zahedan in 2015, were selected and assigned into two groups of intervention and control (50 in each group). Data collection tool was the perceived marital relationship quality components questionnaire. Questionnaires were completed by the both groups before and six weeks after the sex education sessions. Data were analyzed using descriptive and inferential statistics through SPSS software version 20. Results: There was no statistically significant difference between the two groups (P<0.05) in terms of age, the duration of marriage, gestational age and gravidity. In post-test measurement, the mean of the total score of marital relationship quality and components such as satisfaction, sexual excitement, love, commitment, intimacy, and trust, were significantly higher in the intervention group than in the control group. Analysis of covariance also showed that the total score mean for the marital relationship and its components had significant difference in the pregnant women in two groups, after sex education (P<0.001). Conclusion: Given the effectiveness of sex education in the improvement of marital relationship quality in pregnant women, this educational intervention is recommended to be integrated into the education program and prenatal care of pregnant women in order to improve the couple's relationship quality in pregnancy.